2021
DOI: 10.1088/1755-1315/735/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Different Levels of American Cockroach (Periplaneta americana) powder on Productive and Physiological Performance of Japanese Quail (Coturnix japonica)

Abstract: This study aimed to investigate the effect of using different levels of American cockroach (Periplaneta americana) powder on productive and physiological performance of Japanese quail (Coturnix japonica). One hundred and thirty-five, 45 days-old of Japanese quail females were randomly divided into three groups (45 females for each). Each group has three replicates (15 females per each). The groups were included: The first group was fed on experimental diet included with 0 % of insect powder and 6% of protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Insect powder can be added to poultry diets as a source of animal protein. This addition not only does not negatively affect the performance of poultry but can also achieve better results than traditional protein feeds in some aspects ( Elahi et al, 2020 ; Al-Salhie et al, 2021 ). Insect meal meets the nutritional requirements of poultry, providing essential amino acids, high nutrient digestibility, and feed acceptability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insect powder can be added to poultry diets as a source of animal protein. This addition not only does not negatively affect the performance of poultry but can also achieve better results than traditional protein feeds in some aspects ( Elahi et al, 2020 ; Al-Salhie et al, 2021 ). Insect meal meets the nutritional requirements of poultry, providing essential amino acids, high nutrient digestibility, and feed acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…They are very efficient at converting plant feeds into animal proteins, which can help address the issue of animal protein shortages and contribute to achieving food security sustainably ( Boate and Suotonye, 2020 ). Al-Salhie et al (2021) reported that P. americana can be a 100% complete replacement for protein sources without negatively affecting quail performance. In some cases, it can even yield better results than conventional protein feeds while also enhancing the physiological performance of Japanese quail ( Coturnix japonica ).…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous development of the times, traditional physical training is far from being able to meet the current development trend, this requires that during the physical training of wrestlers, incorporating functional strength training, so that athletes can achieve better results. 3 Therefore, the author has an important training period before the 2020 Wrestling Team Games, wrestling coaches should combine theory with practice, select reasonable physiological indicators to monitor athletes, strictly control the training content and exercise intensity of each class, it is of great significance to the improvement of athletes' sports performance. 4…”
Section: Introductionmentioning
confidence: 99%
“…Hatab et al Effect of a dietary inclusion of full-fat or defatted silkworm pupa meal on the nutrient digestibility and faecal microbiome of fattening quails. Dalle Zotte et alResearch,Society and Development, v. 12, n. 1, e21212139386, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i1.39386 4 LH (hormônio luteinizante), além de maior peso de ovários e oviduto, apresentando melhor desempenho fisiológico(Al-Salhie et al, 2021).…”
unclassified